Magnesium phosphate maritime work repair mortar and preparation method thereof
By combining calcium lactate, tributyl phosphate and metakaolin, the setting time of magnesium phosphate repair mortar is extended, and polyvinyl alcohol fibers and refired magnesium oxide is combined, the problem of loose structure of traditional marine building materials in seawater environments is solved. It achieves high strength and good anti-seepage performance to meet the construction needs of marine engineering.
Patent Information
- Application Number
- CN202411065032.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional marine building materials are susceptible to external factors in the seawater environment, and are difficult to meet the strength and operability requirements of marine disaster rescue. The mortar of magnesium phosphate repair is high in the early stage but the condensation time is short, and the dissolution of magnesium oxide in seawater leads to loose structure. Influence mechanical properties.
By combining calcium lactate, tributyl phosphate and metakaolin, the dispersion and reaction sufficiency of magnesium oxide are increased, the coagulation time is extended, and the anti-seepage performance and bonding strength are improved by combining polyvinyl alcohol fibers, and the refired magnesium oxide and nickel are used. Slag sand improves material performance.
It significantly improves the settling time and fluidity of magnesium phosphate marine repair mortar, enhances its compressive, flexural strength and permeability in the marine environment, and ensures the stability and durability of the structure.
Smart Images

Figure BDA0004979092050000081 
Figure BDA0004979092050000091 
Figure BDA0004979092050000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of repair mortar, and in particular relates to a magnesium phosphate marine engineering repair mortar and a preparation method thereof. Background Art
[0002] Due to the erosion of seawater, reinforced concrete structures are prone to failure, which can lead to a decrease in their bearing capacity in severe cases, posing a threat to the safety of the structure. Traditional marine engineering building materials are mainly silicate cement, which has a slow curing speed and is easily affected by external factors such as ambient temperature and humidity, making it difficult to meet the needs of emergency rescue. Marine disaster rescue and emergency rescue have increasingly higher requirements for marine engineering building materials with high strength, strong operability, long storage time, small deformation and good durability.
[0003] Magnesium phosphate repair mortar has good fluidity, high early strength, strong hardening ability under low temperature conditions, and extremely high impermeability, ensuring the adaptability and reliability of marine engineering projects working in extreme environments. It has excellent compatibility with concrete matrix materials, which makes it not only directly used for the repair of existing concrete structures, but also enhances their bonding properties. This unique advantage is particularly prominent in marine engineering. The reaction mechanism of magnesium phosphate repair mortar is an exothermic reaction based on acid-base neutralization, which has the characteristics of fast setting time and high early strength. Because a large amount of heat energy is released by the reaction, the heat energy inside the system accumulates rapidly, resulting in an accelerated reaction rate. If appropriate retarding measures are not taken, the material is likely to solidify in just a few minutes at room temperature, which is a major problem for engineering projects that need to maintain structural stability. In addition, another problem with magnesium phosphate repair mortar is that the dissolution of magnesium oxide and hydration products that do not participate in the reaction in the seawater environment will make the material structure loose. This structural instability not only affects its mechanical properties, but also reduces its strength in seawater, thereby restricting its application in marine engineering.
[0004] Therefore, a new type of magnesium phosphate repair mortar was developed, which effectively improved the fluidity and increased its setting time, so that the magnesium oxide reacted fully, thereby ultimately improving the strength of the prepared repair mortar. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a magnesium phosphate marine engineering repair mortar, which effectively improves its fluidity, increases the setting time, and allows the magnesium oxide to react fully, thereby ultimately improving the strength of the prepared repair mortar.
[0006] Technical solution: The magnesium phosphate marine engineering repair mortar of the present invention includes the following raw materials by weight: 32-38 parts of magnesium oxide, 16-20 parts of potassium dihydrogen phosphate, 1.8-2.0 parts of calcium lactate, 1.7-1.9 parts of early strength agent, 1.6-2.0 parts of tributyl phosphate, 8-10 parts of metakaolin, 0.18-0.22 parts of polyvinyl alcohol fiber, 40-44 parts of mixed sand and 13-16 parts of water.
[0007] The present invention is based on the preparation of magnesium phosphate mortar by magnesium oxide and potassium dihydrogen phosphate, and by compounding calcium lactate and tributyl phosphate, the low surface tension of tributyl phosphate makes magnesium oxide particles fully dispersed in water, reduces the friction between particles, reduces the flow resistance of magnesium phosphate cement slurry, and thus improves the fluidity of the slurry; and based on the addition of tributyl phosphate so that magnesium oxide particles are fully dispersed, combined with calcium lactate that is weakly alkaline in the aqueous solution, the dissolution rate of uniformly dispersed magnesium oxide is slowed down, and the setting time of magnesium phosphate repair mortar is further extended, and magnesium oxide reaction can be made more sufficient, reducing the content of magnesium oxide remaining in the mortar system. The addition of tributyl phosphate can also reduce the surface tension of the solution in the pores, thereby reducing capillary stress, reducing the evaporation of water, and causing the drying shrinkage of magnesium phosphate cement to decrease. The reduction in drying shrinkage reduces the voids inside the mortar, improves the bonding strength of the mortar, and makes the repair mortar not easy to fall off, thereby protecting marine buildings from damage caused by seawater erosion.
[0008] The repair mortar is also compounded with metakaolin, which has a small particle size and is easy to fill the pores of the magnesium phosphate repair mortar. It is easily stimulated by acid and alkali in the magnesium phosphate system to produce a large amount of hydration products. The filling effect of its own particles and its hydration products in the pores of the magnesium phosphate repair mortar can improve the density, improve the seawater erosion resistance and strength of the magnesium phosphate marine engineering repair mortar. In addition, the addition of metakaolin can reduce the internal stress of struvite crystals, which is beneficial to the strength of the magnesium phosphate repair mortar.
[0009] The repair mortar is also compounded with polyvinyl alcohol fibers. The addition of the polyvinyl alcohol fibers can play a good restraining role on the magnesium phosphate repair mortar, effectively reduce the generation of microcracks, slow down the erosion rate of external ions on the repaired concrete, thereby delaying the invasion of harmful substances in the external environment and effectively improving the anti-seepage performance of the repaired concrete.
[0010] Furthermore, the magnesium oxide used in the repair mortar can be dead-burned magnesium oxide, which is obtained by calcining magnesite at 1500-1800° C. for 24-30 hours, with a mass fraction of ≥90% and a particle size of 5-80 μm.
[0011] Furthermore, the early strength agent used in the repair mortar can be at least one of lithium carbonate, calcium formate, sodium chloride or sodium sulfate. Lithium carbonate is preferred. The repair mortar preferably uses lithium carbonate as an early strength agent, which can accelerate the hydration process of the magnesium phosphate repair mortar. As the hydration product increases, the early strength of the composite material increases, which solves the effect of the retarder on the early strength of the repair mortar and ensures the early strength of the marine repair mortar.
[0012] Furthermore, the metakaolin used in the repair mortar is anhydrous aluminum silicate formed by dehydrating kaolin at 600-900°C, with a particle size of ≤20μm.
[0013] Furthermore, the polyvinyl alcohol fiber used in the repair mortar has a length of 8-12 mm, a diameter of 30-40 μm, and an elastic modulus of ≥30 GPa.
[0014] Furthermore, the mixed sand used in the repair mortar is a mixture of natural sand, machine-made sand and nickel slag sand in a weight ratio of 1:(1-2):(0.5-1).
[0015] Furthermore, the nickel slag sand used in the repair mortar has a MgO mass fraction of ≥20%, a CaO mass fraction of ≥6%, and a SiO2 mass fraction of ≥45%, and the nickel slag sand is obtained by crushing the nickel slag at 2-4 levels.
[0016] The method for preparing the magnesium phosphate marine engineering repair mortar of the present invention comprises the following steps:
[0017] (1) mixing calcium lactate, tributyl phosphate and water, and stirring for 45-60 seconds at a stirring rate of 135-145 r / min to obtain a mixed solution;
[0018] (2) stirring magnesium oxide, potassium dihydrogen phosphate, an early strength agent, metakaolin, and polyvinyl alcohol fiber at a stirring rate of 135-145 r / min for 45-60 s to obtain a mixed powder;
[0019] (3) adding the mixed powder of step (2) to the mixed solution of step (1), stirring and reacting at 135-145 r / min for 45-60 s to obtain a mixture;
[0020] (4) Adding the mixed sand to the mixture obtained in step (3), stirring for 60-90 seconds at a stirring rate of 275-295 r / min to obtain magnesium phosphate marine engineering repair mortar.
[0021] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the setting time of the magnesium phosphate marine engineering repair mortar is ≥22min, which meets the time requirements of marine engineering construction; the fluidity is ≥190mm, and the fluidity is good; the 3h compressive strength is ≥28.7MPa, the 3d compressive strength is ≥41.8MPa, the 28d compressive strength is ≥47.5MPa, the 3h flexural strength is ≥4.0MPa, the 3d flexural strength is ≥6.2MPa, and the 28d flexural strength is ≥6.7MPa, and the strength stability is good; the 1d tensile bonding strength is ≥0.94MPa, and the bonding strength is high; the shrinkage rate is ≤0.04%, and the anti-penetration performance is excellent, and it has broad prospects in the application of marine engineering. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described in detail below in conjunction with the embodiments. It should be noted that the raw materials used in the present invention can all be purchased from the market.
[0023] The magnesium oxide used is dead-burned magnesium oxide, which is obtained by calcining magnesite at 1500-1800°C for 24-30h, with a mass fraction of ≥90% and a particle size of 5-80μm. The early strength agent is lithium carbonate with a mass fraction of ≥98.0%. Metakaolin is an anhydrous aluminum silicate formed by dehydrating kaolin at 600-900°C, with a particle size of ≤20μm. The length of the polyvinyl alcohol fiber is 8-12mm, the diameter is 30-40μm, and the elastic modulus is ≥30GPa. The mass fraction of MgO in nickel slag sand is ≥20%, the mass fraction of CaO is ≥6%, and the mass fraction of SiO2 is ≥45%. The nickel slag sand is obtained by crushing the nickel slag at 2-4 levels. The early strength agent can be at least one of lithium carbonate, calcium formate, sodium chloride or sodium sulfate. Lithium carbonate is preferred.
[0024] Example 1
[0025] The component contents of the magnesium phosphate marine engineering repair mortar of Example 1 are shown in Table 1 below.
[0026] Table 1 Component contents of the repair mortar of Example 1
[0027] Serial number Components Weight parts / parts 1 Magnesium oxide 34 2 Potassium dihydrogen phosphate 18 3 Calcium lactate 1.8 4 Lithium carbonate 1.5 5 Polyvinyl alcohol fiber 0.2 6 Metakaolin 8 7 Tributyl phosphate 1.7 8 Mixed sand 40 9 water 13
[0028] The mixed sand used in Example 1 is a mixture of natural sand, machine-made sand and nickel slag sand in a weight ratio of 1:1:0.5.
[0029] The preparation method of the magnesium phosphate marine engineering repair mortar of this embodiment 1 comprises the following steps:
[0030] (1) mixing calcium lactate, tributyl phosphate and water, and stirring for 50 seconds at a stirring rate of 140 r / min to obtain a mixed solution;
[0031] (2) stirring magnesium oxide, potassium dihydrogen phosphate, lithium carbonate, metakaolin, and polyvinyl alcohol fiber at a stirring rate of 140 r / min for 50 s to obtain a mixed powder;
[0032] (3) adding the mixed powder of step (2) to the mixed solution of step (1), stirring and reacting at 140 r / min for 50 s to obtain a mixture;
[0033] (4) Adding the mixed sand to the mixture obtained in step (3), stirring for 80 seconds at a stirring rate of 285 r / min, to obtain magnesium phosphate marine engineering repair mortar.
[0034] Example 2
[0035] The component contents of the magnesium phosphate marine engineering repair mortar of Example 2 are shown in Table 2 below.
[0036] Table 2 Component contents of the repair mortar of Example 2
[0037] Serial number Components Weight parts / parts 1 Magnesium oxide 36 2 Potassium dihydrogen phosphate 16 3 Calcium lactate 1.8 4 Lithium carbonate 1.7 5 Polyvinyl alcohol fiber 0.2 6 Metakaolin 8 7 Tributyl phosphate 1.8 8 Mixed sand 40 9 water 13
[0038] The mixed sand used in Example 2 is a mixture of natural sand, machine-made sand and nickel slag sand in a weight ratio of 1:1:0.5.
[0039] The preparation method of the magnesium phosphate marine engineering repair mortar in Example 2 is the same as that in Example 1.
[0040] Example 3
[0041] The component contents of the magnesium phosphate marine repair mortar of Example 3 are shown in Table 3 below.
[0042] Table 3 Component contents of the repair mortar of Example 3
[0043] Serial number Components Weight parts / parts 1 Magnesium oxide 32 2 Potassium dihydrogen phosphate 20 3 Calcium lactate 1.8 4 Lithium carbonate 1.7 5 Polyvinyl alcohol fiber 0.2 6 Metakaolin 8 7 Tributyl phosphate 1.8 8 Mixed sand 40 9 water 13
[0044] Among them, the preparation methods of the mixed sand and magnesium phosphate marine engineering repair mortar used in Example 3 are the same as those in Example 1.
[0045] Example 4
[0046] The component contents of the magnesium phosphate marine engineering repair mortar of Example 4 are shown in Table 4 below.
[0047] Table 4 Component contents of the repair mortar of Example 4
[0048] Serial number Components Weight parts / parts 1 Magnesium oxide 32 2 Potassium dihydrogen phosphate 20 3 Calcium lactate 2.0 4 Lithium carbonate 1.7 5 Polyvinyl alcohol fiber 0.18 6 Metakaolin 8 7 Tributyl phosphate 1.6 8 Mixed sand 40 9 water 14
[0049] Among them, the preparation methods of the mixed sand and magnesium phosphate marine engineering repair mortar used in Example 4 are the same as those in Example 1.
[0050] Example 5
[0051] The component contents of the magnesium phosphate marine repair mortar of Example 5 are shown in Table 5 below.
[0052] Table 5 Component contents of the repair mortar of Example 5
[0053] Serial number Components Weight parts / parts 1 Magnesium oxide 38 2 Potassium dihydrogen phosphate 19 3 Calcium lactate 2.0 4 Lithium carbonate 1.9 5 Polyvinyl alcohol fiber 0.22 6 Metakaolin 10 7 Tributyl phosphate 2.0 8 Mixed sand 44 9 water 16
[0054] The mixed sand used in Example 5 is a mixture of natural sand, machine-made sand and nickel slag sand in a weight ratio of 1:2:1.
[0055] The preparation method of the magnesium phosphate marine engineering repair mortar of this embodiment 5 comprises the following steps:
[0056] (1) mixing calcium lactate, tributyl phosphate and water, and stirring for 60 seconds at a stirring rate of 135 r / min to obtain a mixed solution;
[0057] (2) stirring magnesium oxide, potassium dihydrogen phosphate, lithium carbonate, metakaolin, and polyvinyl alcohol fiber at a stirring rate of 135 r / min for 60 s to obtain a mixed powder;
[0058] (3) adding the mixed powder of step (2) to the mixed solution of step (1), stirring and reacting at 135 r / min for 60 s to obtain a mixture;
[0059] (4) Adding the mixed sand to the mixture obtained in step (3), stirring for 90 seconds at a stirring rate of 275 r / min, to obtain magnesium phosphate marine engineering repair mortar.
[0060] Example 6
[0061] The component contents of the magnesium phosphate marine engineering repair mortar of Example 6 are shown in Table 6 below.
[0062] Table 6 Component contents of the repair mortar of Example 6
[0063] Serial number Components Weight parts / parts 1 Magnesium oxide 36 2 Potassium dihydrogen phosphate 20 3 Calcium lactate 1.9 4 Lithium carbonate 1.8 5 Polyvinyl alcohol fiber 0.2 6 Metakaolin 8 7 Tributyl phosphate 1.8 8 Mixed sand 40 9 water 13
[0064] Among them, the mixed sand used in Example 6 is a mixture of natural sand, machine-made sand and nickel slag sand in a weight ratio of 1:2:1.
[0065] The preparation method of the magnesium phosphate marine engineering repair mortar of Example 6 comprises the following steps:
[0066] (1) mixing calcium lactate, tributyl phosphate and water, and stirring for 45 seconds at a stirring rate of 145 r / min to obtain a mixed solution;
[0067] (2) stirring magnesium oxide, potassium dihydrogen phosphate, lithium carbonate, metakaolin, and polyvinyl alcohol fiber at a stirring rate of 145 r / min for 45 seconds to obtain a mixed powder;
[0068] (3) adding the mixed powder of step (2) to the mixed solution of step (1), stirring and reacting at 145 r / min for 45 seconds to obtain a mixture;
[0069] (4) Adding the mixed sand to the mixture obtained in step (3), stirring for 60 seconds at a stirring rate of 295 r / min, to obtain magnesium phosphate marine engineering repair mortar.
[0070] Comparative Example 1
[0071] The basic raw material components of Comparative Example 1 are the same as those of Example 6, except that tributyl phosphate is not added. The specific raw materials are shown in Table 7 below.
[0072] Table 7 Component contents of the repair mortar of Comparative Example 1
[0073] Serial number Components Weight parts / parts 1 Magnesium oxide 36 2 Potassium dihydrogen phosphate 20 3 Calcium lactate 1.9 4 Lithium carbonate 1.8 5 Polyvinyl alcohol fiber 0.2 6 Metakaolin 8 7 Tributyl phosphate - 8 Mixed sand 40 9 water 13
[0074] Comparative Example 2
[0075] The basic raw material components of Comparative Example 2 are the same as those of Example 6, except that fly ash is used instead of kaolin. The specific raw materials are shown in Table 8 below.
[0076] Table 8 Component content of the repair mortar of Comparative Example 2
[0077]
[0078]
[0079] Comparative Example 3
[0080] The basic raw material components of Comparative Example 3 are the same as those of Example 6, except that the raw materials are a mixture of natural sand and machine-made sand in a weight ratio of 1:2. The specific raw materials are shown in Table 9 below.
[0081] Table 9 Component contents of the repair mortar of Comparative Example 3
[0082] Serial number Components Weight parts / parts 1 Magnesium oxide 36 2 Potassium dihydrogen phosphate 20 3 Calcium lactate 1.9 4 Lithium carbonate 1.8 5 Polyvinyl alcohol fiber 0.2 6 Metakaolin 8 7 Tributyl phosphate 1.8 8 Mixed sand 40 9 water 13 5 Polyvinyl alcohol fiber 0.2 6 Metakaolin 8 7 Tributyl phosphate 1.8 8 Mixed sand 40 9 water 13
[0083] Performance Testing
[0084] The setting time of magnesium phosphate repair mortar is determined in accordance with JGJ / T70-2009 "Standard Test Method for Basic Performance of Building Mortar". The fluidity of magnesium phosphate repair mortar is determined in accordance with GB / T2419-2005 "Method for Determination of Fluidity of Cement Mortar". The flexural and compressive strength (3h, 3d, 28d) of magnesium phosphate repair mortar is determined in accordance with GB / T17671-2021. The 1d tensile bond strength of magnesium phosphate repair mortar is determined in accordance with JGJ / T70-2009 "Standard Test Method for Basic Performance of Building Mortar". The shrinkage rate of magnesium phosphate repair mortar is determined in accordance with JC / T603-2004 "Test Method for Shrinkage of Cement Mortar". The obtained measurement results are shown in Table 11.
[0085] Table 11 Performance test table of Examples 1-6 and Comparative Examples 1-4
[0086]
[0087] It can be seen from Table 11 that the setting time of the repair mortar is ≥22min, which meets the time requirement of marine engineering construction; the fluidity is ≥190mm, and the fluidity is good; the 3h compressive strength is ≥28.7MPa, the 3d compressive strength is ≥41.8MPa, the 28d compressive strength is ≥47.5MPa, the 3h flexural strength is ≥4.0MPa, the 3d flexural strength is ≥6.2MPa, and the 28d flexural strength is ≥6.7MPa, and the strength stability is good; the 1d tensile bond strength is ≥0.94MPa, and the bond strength is high; the shrinkage rate is ≤0.04%, and the anti-penetration performance is excellent, which has broad prospects in the application of marine engineering.
Claims
1. A magnesium phosphate marine engineering repair mortar, characterized in that: The raw materials include the following by weight: 32-38 parts of magnesium oxide, 16-20 parts of potassium dihydrogen phosphate, 1.8-2.0 parts of calcium lactate, 1.5-1.9 parts of early strength agent, 0.18-0.22 parts of polyethanol fiber, 8-10 parts of metakaolin, 1.6-2.0 parts of tributyl phosphate, 40-44 parts of mixed sand and 13-16 parts of water.
2. The magnesium phosphate marine engineering repair mortar according to claim 1, characterized in that: The magnesium oxide is dead-burned magnesium oxide, which is obtained by calcining magnesite at 1500-1800° C. for 24-30 hours, with a mass fraction of ≥90% and a particle size of 5-80 μm.
3. The magnesium phosphate marine engineering repair mortar according to claim 1, characterized in that: The early strength agent includes at least one of lithium carbonate, calcium formate, sodium chloride or sodium sulfate.
4. The magnesium phosphate marine engineering repair mortar according to claim 1, characterized in that: The metakaolin is anhydrous aluminum silicate formed by dehydrating kaolin as a raw material at 600-900° C., and the particle size is ≤20 μm.
5. The magnesium phosphate marine engineering repair mortar according to claim 1, characterized in that: The polyvinyl alcohol fiber has a length of 8-12 mm, a diameter of 30-40 μm, and an elastic modulus of ≥30 GPa.
6. The magnesium phosphate marine engineering repair mortar according to claim 1, characterized in that: The mixed sand is a mixture of natural sand, machine-made sand and nickel slag sand in a weight ratio of 1:(1-2):(0.5-1).
7. The magnesium phosphate marine engineering repair mortar according to claim 6, characterized in that: The nickel slag sand has a MgO mass fraction of ≥20%, a CaO mass fraction of ≥6%, and a SiO2 mass fraction of ≥45%. The nickel slag sand is obtained by crushing the nickel slag in 2-4 stages.
8. A method for preparing the magnesium phosphate marine repair mortar according to claim 1, characterized in that: The steps include: (1) mixing tributyl phosphate and water, and stirring for 45-60 seconds at a stirring rate of 135-145 r / min to obtain a mixed solution; (2) stirring magnesium oxide, potassium dihydrogen phosphate, calcium lactate, an early strength agent, metakaolin, and polyvinyl alcohol fiber at a stirring rate of 135-145 r / min for 45-60 s to obtain a mixed powder; (3) adding the mixed powder of step (2) to the mixed solution of step (1), stirring and reacting at 135-145 r / min for 45-60 s to obtain a mixture; (4) Adding the mixed sand to the mixture obtained in step (3), stirring for 60-90 seconds at a stirring rate of 275-295 r / min to obtain magnesium phosphate marine engineering repair mortar.
